Financial access of midstream agricultural firms in Africa: Evidence from the LSMS-ISA and World Bank enterprise surveys - Ambler, Kate; de Brauw, Alan; Herskowitz, Sylvan; Pulido, Cristhian (International Food Policy Research Institute, 2022)
The midstream of agricultural value chains are rapidly changing in response to shifting domestic and international demand. While the performance of this segment may have important implications for the entire sector, evidence on midstream actors and their financial needs remain thin. We use data from both the Living Standards Measurement Study – Integrated Surveys on Agriculture and the World Bank Enterprise Survey from seven African countries to identify these agricultural midstream firms and assess their access to formal credit, comparing them to other, non-agricultural midstream firms. We find that the identified agricultural midstream firms are larger and more productive than their non-agricultural midstream counterparts and are less likely to report barriers to accessing credit, though overall access levels remain low. Among agricultural midstream firms, those owned or managed by women are more likely to report barriers to accessing credit. Taken together, these findings help build our understanding about the financial needs of micro-, small-, and medium-size enterprises in the agricultural midstream.